JURIDICAL ANALYSIS OF THE LEGAL PROTECTION OF SONG ROYALTIES AGAINST COPYRIGHT INFRINGEMENT DISPUTES - Atik Abawaiki; Asri Elies Alamanda (Awang Long Law Review, 2026)
Copyright provides exclusive rights and legal protection, especially to industry players to get rewards in the form of royalties for their creations, which is currently an interesting issue in the country's music industry. One of the most pressing issues in protecting IP in the digital age is the enforcement of music royalties in cases of copyright infringement. This research is designed with the aim of exploring further legal protection of royalty practices and concepts in the context of copyright infringement disputes in Indonesia. The moral and economic rights of creators must be fully protected when music is considered intellectual property. The main legal basis for royalty management is UUHC Number 28 of 2014 and Government Regulation Number 56 of 2021, which aim to ensure that creators receive financial rewards from the commercial use of their works. The National Collective Management Institute (LMKN) is responsible for managing royalties and ensuring that creators and rights holders receive and receive a proportional share. The main challenge is the number of copyright infringements due to the lack of awareness of music industry players regarding royalty payment obligations. This research also discusses the mechanism for resolving royalty disputes through non-litigation alternatives and litigation in the Commercial Court to provide legal certainty and effective protection. With a normative and juridical approach, this research aims to strengthen the implementation of song copyright law and encourage a fair and sustainable music industry in Indonesia.